Yard, street, park : - Girling, Cynthia L. (John Wiley & Sons, 1994)
Most American suburban housing was planned as a product, not as a community. This book examines the problems and challenges of suburban development and proposes a solution: the design of well-connected networks of open space linking the private world of yards to parks of all scales, from neighborhood playgrounds, to local, regional, state and national park systems, using greenways and streets that allow safe pedestrian and bike traffic.